A survey of the school libraries and audiovisual centers administered by the Missionary Sisters of the Immaculate Conception with implications for development planning - Gumnad, Ma. Socorro G.; Picache, Ursula G.; Buenrostro, Juan Jr. C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1987)
The survey of the school libraries and audiovisual centers administered by the Missionary Sisters of the Immaculate Conception (MIC) aimed to gather salient information about the present condition of these institutions. The survey intended to find out the extent of development of the library and audiovisual centers by looking into the: 1) statement of objectives; 2) library personnel; 3) budget and sources of financial support; 4) the collection; 5) organization of the collection; 6) library/audiovisual programs and services; and the 7) equipment, facilities and quarters. The findings are meant to serve as bases for recommending improvements, if necessary, in these libraries and audiovisual centers.
Two questionnaires were formulated to gather data. One was addressed to the print and nonprint librarian of each school and other was addressed to the members of the faculty. The schools were visited and the administrator/s, the print and nonprint librarians, and some faculty members were interviewed. All the available documents were read. The returns were then collated, analyzed and interpreted. Among the significant findings of this study are:1) The Immaculate Conception Academy (ICA) library and audiovisual center are organized into the Educational Media Center (EMC) while the library and the audiovisual center of the Immaculate Conception Academy of Manila (ICAM) remain as separate entities. The Immaculate Heart of Mary Academy (IHMA) has no organized audiovisual center yet.
Only the EMC at ICA has a printed manual of information that gives complete data on the purposes, functions, policies, procedures and personnel of the library and audiovisual center.2) The three school librarians of the print collection are professionally qualified but not equally updated. The audiovisual librarian of ICAM is not professionally qualified.
The salary of the librarians depends upon the capacity of the school to pay and upon the status given them, hence their salaries differ.3) ICA has the largest library staff complement while IHMA has the smallest.4) At ICA the print and nonprint librarians prepare the budget and exercise decision-making such as the purchase of materials, but at ICAM and IHMA the librarians do not prepare the budget and have not much participation in decision-making.5) The budget for the library and the AV center in the three schools defer considerably, with ICA having the largest budget and ICAM the smallest.6) The library and AV fees charged the students vary in the three schools. As expected ICA charges the highest fees while IHMA charges the lowest.7) The ICA library has the largest book collection while the IHMA library has the smallest collection. ICA also has the largest periodical collection. Most of the books in the three libraries are more than ten years old and so are the audiovisual materials and equipment.8) The services in the school libraries and audiovisual centers depend upon the library personnel. Only the EMC at ICA has a program of library instruction in addition to faculty and student orientation.9) Very few teachers use the library and audiovisual center in the three schools. Most of the respondents use the library only once a week.10) The library and AV center space/quarters are still inadequate. Only IHMA has provided space for expansion of the library/AV center in its 5-year development plan.
From the data gathered by the survey, it can be concluded that the school libraries differ in their development in all aspects. Only ICA has defined its purposes and written these in the EMC Manual of Information.
The library/AV center fee of ICAM and IHMA are very low, therefore there is a need to seek other sources of financial support for the libraries/audiovisual centers. Although the libraries have been in operation for more than forty years, their collections of books and periodicals are still very limited. The lack of a written selection and acquisition policy has contributed to the unbalanced collections in two schools.
Mimeographed.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: School libraries -- Philippines -- Evaluation; Audiovisual library service -- Philippines